IPTEKS PENGHITUNGAN NILAI MARKET VALUE ADDED ATAS KEPUTUSAN INVESTASI - Thomas, Mario Yohanis (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2020)
Development in technology has triggered the aggresivity of stock practitioners to make transactions in the stock market, so the portofolio analyzing skill is in high demand. This article practically explains about the implementation of Market Value Added (MVA) to support decision-making for investors. The formula is applied to 10 sample of public corporations listed in the Indonesia Stock Exchange. The results show that 6 firms have a positive MVA value, therefore they are fundamentally good for investing. On the other hand, the remaining 4 are showing MVA values below 0 because they are not able to gain company value above their total investment.